Leo Wolman papers - Wolman, Leo, 1890-1961.
Correspondence, reports, financial worksheets and graphs, wage rates material, bibliographies, election results for the U.S. National Labor Relations Board, press releases, printed matter, and other papers relating to Wolman's career as an economist. Subjects include labor unions in Great Britain and the United States; labor unions in the construction industry, manufacturing industries, mineral industries, professions, public transportation, public utilities, and service industries; state labor boards; and the U.S. National War Labor Board.
Economist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: United States. -- National Labor Relations Board; United States. -- National War Labor Board (1918-1919); Construction industry -- Employees -- Labor unions; Arbitration, Industrial -- Great Britain; Arbitration, Industrial -- United States; Economics; Industrial relations -- Great Britain; Industrial relations -- United States; Industries -- Great Britain; Industries -- United States; Labor; Labor laws and legislation -- Great Britain; Labor laws and legislation -- United States; Labor unions -- Great Britain; Labor unions -- United States; Manufacturing industries -- Employees -- Labor unions; Mineral industries -- Employees -- Labor unions; Professional employees -- Labor unions; Public utilities -- Employees -- Labor unions; Service industries workers -- Labor unions; Transport workers -- Labor unions; Economists